Geothermal Assessment of Target Formations Using Recorded Temperature Measurements for the Alberta No. 1 Geothermal Project - Katherine Y. Huang; Catherine J. Hickson; Darrell Cotterill; Yannick Champollion (Applied Sciences, 2021)
The Alberta No. 1 project is a planned power and heat (direct use) geothermal project located within the County of Grande Prairie and Municipal District of Greenview. For the project to successfully produce power and heat on a commercial scale, temperatures of 120 °C are desirable. The produced fluids must also be from highly permeable formations from depths of less than 4500 m. Bottomhole temperature measurements and wireline logs from Alberta’s extensive oil and gas database were used to determine the depths to target formations and temperatures within these formations in the project area. The target formations include the dolomitized carbonate units of Devonian age from the Beaverhill Lake Group to the top of the Precambrian Basement. Permeable Devonian-aged sandstone units such as the Granite Wash Formation are also targets. Results suggest that elevation to the top of the Beaverhill Lake Group range from 3104 m to 4094 m and temperatures at the top of the formation range from 87 °C to 123 °C in the study area. Elevation to the top of the Precambrian Basement ranges from 3205 m to 4223 m and temperatures at the formation top range from 74 °C to 124 °C. Within the area where Alberta No. 1 plans to drill, temperatures close to and exceeding 120 °C are expected within the target formations.